The sub-annual breeding cycle of a tropical seabird. - S James Reynolds; Graham R Martin; Alistair Dawson; Colin P Wearn; B John Hughes (PLoS ONE)
Breeding periodicity allows organisms to synchronise breeding attempts with the most favourable ecological conditions under which to raise offspring. For most animal species, ecological conditions vary seasonally and usually impose an annual breeding schedule on their populations; sub-annual breeding schedules will be rare. We use a 16-year dataset of breeding attempts by a tropical seabird, the sooty tern (Onychoprion fuscatus), on Ascension Island to provide new insights about this classical example of a population of sub-annually breeding birds that was first documented in studies 60 years previously on the same island. We confirm that the breeding interval of this population has remained consistently sub-annual. By ringing >17,000 birds and re-capturing a large sample of them at equivalent breeding stages in subsequent seasons, we reveal for the first time that many individual birds also consistently breed sub-annually (i.e. that sub-annual breeding is an individual as well as a population breeding strategy). Ascension Island sooty terns appear to reduce their courtship phase markedly compared with conspecifics breeding elsewhere. Our results provide rare insights into the ecological and physiological drivers of breeding periodicity, indicating that reduction of the annual cycle to just two life-history stages, breeding and moult, is a viable life-history strategy and that moult may determine the minimum time between breeding attempts.